Resposta da comunidade de anuros de Serrapilheira ao gradiente de sucessão ecológica em um fragmento de floresta atlântica interior da região sudeste do Brasil - Alberto Anibal Carosini Vera (2013)
Many human activities result in deforestation and changes in structural characteristics of forests, this process is even greater in Hotspots such as the Brazilian Atlantic Forest. Although the effects of deforestation are well known, yet little is understood in tropical regions about the dynamics of ecological succession and biodiversity. Amphibians are the vertebrates with the highest proportion of endangered species. In tropical forests, amphibians have complex responses to environmental changes caused by human activities, the autoecology of amphibians in the wild is poorly known. This study aimed to describe and compare the richness, composition and relative abundance of species of leaf litter anuran communities in forest areas at different stages of ecological succession, and seek and describe relationships among community structure of leaf litter anurans and the structural characteristics of the forest. Along the 12 samples were collected 337 individuals, 7 species of anurans of leaf litter, belonging to 5 families. The richness was of 5 species in Regeneration area, Early Secondary Forest, Late Secondary Forest and 6 species in Primary Forest. Of the 7 species registered, 4 occurred in all successional stages, with two species, Ischnocnema verrucosa and Leptodactylus spixi, with only an individual collected. The estimated richness (Chao1 Estimator) in the Regeneration Area (Estimated Wealth = 5, SD ± 0.17), the Initial Secondary Forest (estimated Wealth = 5, SD ± 0.45) and the Late Secondary Forest (Estimated Wealth = 5, SD ± 0.25) was equal to the number of species observed; the number of species estimated for the Primary Forest was 8 species (SD ± 3.74). The NMDS and Anosim showed grouping of plots (R = 0.2731, p = 0.037) in accordance to the species composition. The relative abundances of species present in the Regeneration Area sets to the geometric series model Motomura; the relative abundance in Initial Secondary Forest matched the Brokenstick or Null Model, and the relative abundance of species of Primary Forest set to Log-Normal Model. At every stage there was dominance of species Proceratophrys boiei and Rhinella pombali. The Contrast Analysis en the GLM showed a significantly difference between two groups of plots (Deviance = 78,998, p = 2,512 e-5). Litter depth is correlated with the species composition (r2 = 0.5274, p = 0.03019). A tendency to an increase of richness and abundance in more advanced stages of succession, species composition was correlated only with the leaf litter depth, important as habitat, breeding area, refuge and feeding for these amphibians.